Population-scale sequencing resolves determinants of persistent EBV DNA - Sherry S. Nyeo; Erin M. Cumming; Oliver S. Burren; Meghana S. Pagadala; Jacob C. Gutierrez; Thahmina A. Ali; Laura C. Kida; Yifan Chen; Hoyin Chu; Fengyuan Hu; Xueqing Zoe Zou; Benjamin Hollis; et al. (Nature, 2026)
Abstract Epstein–Barr virus (EBV) is an endemic herpesvirus implicated in autoimmunity, cancer and neurological disorders. Although primary infection is often subclinical, persistent EBV infection can drive immune dysregulation and long-term complications. Despite the ubiquity of infection, the determinants of EBV persistence following primary exposure remain poorly understood, although human genetic variation partially contributes to this phenotypic spectrum 1–3 . Here we demonstrate that existing whole genome sequencing (WGS) data of human populations can be used to quantify persistent EBV DNA. Using WGS and health record data from the UK Biobank ( n = 490,560) and All of Us ( n = 245,394), we uncover reproducible associations between blood-derived EBV DNA quantifications and respiratory, autoimmune, neurological and cardiovascular diseases. We evaluate genetic determinants of persistent EBV DNA via genome association studies, revealing heritability enrichment in immune-associated regulatory regions and protein-altering variants in 148 genes. Single-cell and pathway level analyses of these loci implicate variable antigen processing as a primary determinant of EBV DNA persistence. Further, relevant gene programs were enriched in B cells and antigen-presenting cells, consistent with their roles in viral reservoir and clearance. Human leukocyte antigen genotyping and predicted viral epitope presentation affinities implicate major histocompatibility complex class II variation as a key modulator of EBV persistence. Together, our analyses demonstrate how re-analysis of human population-scale WGS data can elucidate the genetic architecture of viral DNA persistence, a framework generalizable to the broader human virome 4 .